When people start getting real: The Group Living Skills Survey for extreme work environments - Landon, Lauren Blackwell; Miller, Jennifer C. W.; Bell, Suzanne T.; Roma, Peter G. (Frontiers in Psychology, 2024)
Introduction Group living skills (GLS), that is, being tidy and considerate of others, are an important skillset for teams who live and work together. However, this construct does not have a validated measure to enable an understanding of how group living skills influence team dynamics over time. We developed and validated a short measure of group living skills for teams living in extreme work environments. Methods We collected data from 83 individuals in 24 teams living and working in space and spaceflight analog environments on missions of 45–240 days. Results We provide evidence of reliability and validity for the GLS Survey over time and identify a two-factor structure. We also demonstrate its use as a measure of team-level dynamics and its utility as a sociometric measure to identify a person’s degree of group living skills. Discussion We outline recommendations for using this new measure in future research and applied settings to understand this unique aspect of teams living and working together.